PENGARUH SOSIALISASI POLITIK OLEH KPU KABUPATEN BANGKA BARAT PERIODE 2013 – 2018 TERHADAP KESADARAN POLITIK PEMILIH DI KECAMATAN MUNTOK KABUPATEN BANGKA BARAT - fany - lestari (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
Elections are one manifestation of democracy where people participate in directly choosing their leaders and participating in determining policies that will determine which direction the country will be taken. In the period 2013 - 2018, the 2014 legislative elections, the 2014 presidential elections, the 2015 regent election and the 2017 gubernatorial elections, there was a decline in voter turn out in Muntok District, West Bangka Regency. Therefore the author wants to know how political socialization is carried out by the General Election Commission of the Regency West Bangka in its efforts to raise public political awareness that will contribute to voter turn out in elections in the end. The research was conducted with a quantitative approach with an instrument in the form of a questionnaire that will be distributed to voters in the 2019 Final Voters List in Muntok District, West Bangka Regency. Determination of the sample using cluster sampling consisting of 7 villages / kelurahan namely tanjung as many as 29 people, sungai baru as many as 13 people, sungai daeng as many as 17 people, belo laut as many as 23 people, air belo as many as 8 people, air limau as much as 4 people and air putih many as 6 people, a total sample of 100 people. Based on the results of distributing questionnaires to voters, it was concluded that the General Election Commission of West Bangka Regency had carried out political socialization that does not build adequate political awareness, only 32,5 %.